Study on dynamic deformation synchronized measurement technology of double-layer liquid surfaces. (November 2017) - Tang, Huiying; Dong, Huimin; Liu, Zhanwei
Highlights: Dynamic deformation synchronized measurement of double-layer liquid surfaces is proposed. Wavefront distortion of double-wavelength transmission light with GPA method is proposed. It can also achieve the accurate measurement of transparent double-sided solid specimens. Abstract: Accurate measurement of the dynamic deformation of double-layer liquid surfaces plays an important role in many fields, such as fluid mechanics, biomechanics, petrochemical industry and aerospace engineering. It is difficult to measure dynamic deformation of double-layer liquid surfaces synchronously for traditional methods. In this paper, a novel and effective method for full-field static and dynamic deformation measurement of double-layer liquid surfaces has been developed, that is wavefront distortion of double-wavelength transmission light with geometric phase analysis (GPA) method. Double wavelength lattice patterns used here are produced by two techniques, one is by double wavelength laser, and the other is by liquid crystal display (LCD). The techniques combine the characteristics such as high transparency, low reflectivity and fluidity of liquid. Two color lattice patterns produced by laser and LCD were adjusted at a certain angle through the tested double-layer liquid surfaces simultaneously. On the basis of the refractive indexes difference of two transmitted lights, the double-layer liquid surfaces were decoupled with GPA method. Combined with the derived relationship between phase variation of transmission-lattice patterns and out-of plane heights of two surfaces, as well as considering the height curves of the liquid level, the double-layer liquid surfaces can be reconstructed successfully. Compared with the traditional measurement method, the developed method not only has the common advantages of the optical measurement methods, such as high-precision, full-field and non-contact, but also simple, low cost and easy to set up.